Comparative analysis of intestinal flora at different overwintering periods in wild relict gulls (Larus relictus): first evidence from Northern China - Yao, Hongyu; Zhang, Zeming; Wu, Nan; Wang, Mengping; Wu, Qian; Wu, Hong; Zhao, Dapeng (Frontiers in Microbiomes, 2023)
The migratory bird's gut microbiome composition and function change during the overwintering period, helping the host to adapt to different environments. Our study investigated the gut microbiome of migratory relict gulls (Larus relictus) in the early and late wintering stages from their overwintering grounds in Tianjin, China. We collected 24 and 29 fecal samples at the early and late stages, respectively, and analyzed the samples using high-throughput sequencing technology to find the relationship between diet, living environment, and gut microbiome of migratory birds. The results showed that the diversity and abundance of microbial communities (alpha diversity) increased during the overwintering period and significantly differed between both groups (beta diversity). Based on the gut microbial taxonomic composition, the relative abundance of Firmicutes decreased during the overwintering period, and Proteobacteria increased significantly. Furthermore, Catellicoccus and Breznakia were the main genera in both the early and late stages. Prediction of KEGG functions based on the PICRUSt2 method showed that changes in the gut microbiome resulted in an increased 2 This is a provisional file, not the final typeset article abundance of bacteria associated with amino acid metabolism, metabolism of cofactors and vitamins, energy metabolism, and environmental adaptation in the late stage. Differences in diet and environment at different stages during the overwintering period may have led to the differentiation of microbial communities, and their adaptive mechanisms need to be further investigated. This is the first in-depth study of the gut microbial composition of L. relictus during the overwintering period in northern China. These findings may contribute to the protection of migratory birds.